ANALISIS KESALAHAN GRAMATIKA DALAM LOMBA PIDATO BAHASA ARAB DI PONDOK PESANTREN MADRASATUL QUR’AN TEBUIRENG JOMBANG - Taufiki Ali Ilhami; Lailatul Qomariyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. his study aims to analyze grammatical errors that occur in the Arabic speech competition at Pondok Pesantren Tebuireng, Jombang. The speech competition serves as one of the means for students (santri) to enhance their spoken Arabic proficiency. However, in practice, grammatical errors are often found that can affect both the meaning and quality of speech delivery. Grammatical errors can be referred to as deviations or mismatches in the use of Arabic grammar rules (nahwu) and morphology (sharaf). These errors include inaccuracies in the use of i’rab (case endings), sentence structure (jumlah ismiyyah and jumlah fi’liyyah), subject-predicate agreement (fa’il and fi’il), verb form usage, and the selection of word forms (singular, dual, and plural). In delivering a speech, a solid understanding of grammar within the Arabic speech text is essential. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that grammatical errors in the Arabic speech competition at Madrasatul Qur’an Tebuireng Jombang mainly stem from mistakes in the use of nahwu (Arabic grammar), especially in i’rab (word endings) and sentence structures (jumlah ismiyyah and jumlah fi’liyyah). Factors influencing these grammatical errors include internal factors such as the participants' lack of mastery of nahwu and sharaf, limited vocabulary understanding, and insufficient muhadatsah (speaking) practice. External factors include an unsupportive environment, inadequate learning facilities and media, and a lack of intensive guidance or coaching.